PENERAPAN SISTEM PENDUKUNG KEPUTUSAN SEKOLAH MENENGAH PERTAMA DI KABUPATEN MINAHASA SELATAN MENGGUNAKAN METODE SAW - Claudio Dandi J Paisa; Nelson Nainggolan; Winsy Christo Deilan Weku (Indonesian Journal of Intelligence Data Science, 2024)
The development of internet technology today is growing rapidly. The internet makes it easier for humans to access information and do various things, we can find the information we need and expand communication networks with technological sophistication, as well as information on junior high schools in South Minahasa district which is still less effective. The purpose of this study was to create a website-based decision support system for junior high schools in South Minahasa district as a means of information for parents and students. The method used in designing this system is the waterfall method. The resulting program is a decision support system for junior high schools in South Minahasa district.